Crossed brainstem syndrome revealing bleeding brainstem cavernous malformation: an illustrative case - Beucler, Nathan (BMC Neurol, 2021)
BACKGROUND: Since the nineteenth century, a great variety of crossed brainstem syndromes (CBS) have been described in the medical literature. A CBS typically combines ipsilateral cranial nerves deficits to contralateral long tracts involvement such as hemiparesis or hemianesthesia. Classical CBS seem in fact not to be so clear-cut entities with up to 20% of patients showing different or unnamed combinations of crossed symptoms. In terms of etiologies, acute brainstem infarction predominates but CBS secondary to hemorrhage, neoplasm, abscess, and demyelination have been described. The aim of this study was to assess the proportion of CBS caused by a bleeding episode arising from a brainstem cavernous malformation (BCM) reported in the literature. CASE PRESENTATION: We present the case of a typical Foville syndrome in a 65-year-old man that was caused by a pontine BCM with extralesional bleeding. Following the first bleeding episode, a conservative management was decided but the patient had eventually to be operated on soon after the second bleeding event. DISCUSSION: A literature review was conducted focusing on the five most common CBS (Benedikt, Weber, Foville, Millard-Gubler, Wallenberg) on Medline database from inception to 2020. According to the literature, hemorrhagic BCM account for approximately 7 % of CBS. Microsurgical excision may be indicated after the second bleeding episode but needs to be carefully weighted up against the risks of the surgical procedure and openly discussed with the patient. CONCLUSIONS: In the setting of a CBS, neuroimaging work-up may not infrequently reveal a BCM requiring complex multidisciplinary team management including neurosurgical advice. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12883-021-02223-7.